The roots of the Libyan-Chadian conflict on Ouzou - Karim, Ghassan Nasser Abdul Hussein; Abood, Wasan Saeed (Al-Adab Journal, 2021)
The Libyan- Chad dispute over Aouzou strip constituted an important stage in the political history of North Africa with the resulting interactions in international relations whether on the regional or international levels.The study reached at the role played by the major countries in ending the Libyan- Chad conflict in favor of the party that stands with their interests, especially France, USA and the role of the two countries in the settlement of the military conflict in favor of Chad.